COVID-19 among heart transplant recipients in Germany: a multicenter survey - Rivinius, Rasmus; Kaya, Ziya; Schramm, René; Boeken, Udo; Provaznik, Zdenek; Heim, Christian; Knosalla, Christoph; Schönrath, Felix; Rieth, Andreas; Berchtold-Herz, Michael; Barten, Markus Johannes; Rauschning, Dominic; et al. (Clinical research in cardiology, 2020)
Heart transplantation may represent a particular risk factor for severe coronavirus infectious disease 2019 (COVID-19) due to chronic immunosuppression and frequent comorbidities. We conducted a nation-wide survey of all heart transplant centers in Germany presenting the clinical characteristics of heart transplant recipients with COVID-19 during the first months of the pandemic in Germany.
Gesehen am 06.12.2021